Analyzing Hadith Sanad Validity: Steps to Assess Acceptance and Authenticity - Nuraini, Nuraini (El-Sunan: Journal of Hadith and Religious Studies, 2024)
Hadith does not possess the same textual certainty (qath'i al-wurud) and argument certainty (qath'i al-dalalah) as the Qur'an. Therefore, the discipline of hadith science was developed to ensure the authenticity of hadith through sanad (chain of transmission) and matan (content) criticism. Sanad criticism focuses on tracing the origin of hadith based on its narrators, while matan criticism evaluates the content of the text. This article aims to identify and verify the quality and authenticity of hadith by conducting an in-depth analysis of the sanad and matan. By exploring the characteristics and credibility of the narrators and the integrity of their transmission chain, the study distinguishes between sahih, hasan, and dha'if hadith based on authenticity and content relevance. Through the science of Takhrij al-Hadith, this research demonstrates that the validation of hadith authenticity is an essential and ongoing effort to preserve and understand the authentic teachings of Islam. The study also emphasizes the importance of Jarh wa Ta’dil in determining the fairness and precision of narrators, as well as investigating shudhudh (inconsistencies) and 'illat (hidden defects) in hadith.